A Comparative Study of Opinions on Executives’ Communication Styles and Representatives’ Performance: A Case Study of Thai Life Insurance Public Company Limited - Kiratianantabwon, Klaothip; Rotjam, Chumphon (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
This study had two main objectives: (1) to examine the level of agents’ opinions regarding executives’ communication styles, and (2) to examine the level of agents’ opinions regarding their performance. This research employed a quantitative approach, with a sample of 400 respondents comprising life insurance agents and sales executives from Thai Life Insurance Public Company Limited. A questionnaire was used as the research instrument, with an Index of Item-Objective Congruence (IOC) of 0.777. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The results revealed that the overall level of executives’ communication styles was moderate. Among the dimensions, supportive communication had the highest mean score, followed by two-way communication, motivational communication, and strategic communication, respectively. Similarly, the overall level of agents’ performance was also moderate, with sales performance rated higher than job satisfaction and agent retention. These findings indicate a perceived role of executive communication that may guide the improvement of management strategies to enhance agents’ performance in the long term.